Cadmium and/or copper excess induce interdependent metal accumulation, DNA methylation, induction of metal chelators and antioxidant defences in the seagrass Zostera marina. (June 2019) - Greco, Maria; Sáez, Claudio A.; Contreras, Rodrigo A.; Rodríguez-Rojas, Fernanda; Bitonti, M. Beatrice; Brown, Murray T.
Abstract: In this investigation, we assessed the effects of Cu and/or Cd excess on physiological and metabolic processes of the widespread seagrass Zostera marina . Adult were exposed to low Cd and Cu (0.89 and 0.8 μM, respectively) and high Cd and Cu (8.9 and 2.4 μM, respectively) for 6 d at: Control conditions; low Cu; high Cu; low Cd; high Cd; low Cd and low Cu; and high Cd and high Cu. Photosynthetic performance decreased under single and combined treatments, although effects were more negative under Cu than Cd. Total Cu accumulation was higher than Cd, under single and combined treatments; however, their accumulation was generally lower when applied together, suggesting competition among them. Levels of glutathione (GSH) and phytochelatins (PCs) followed patterns similar to metal accumulation, with up to PC5, displaying adaptations in tolerance. A metallothionein ( MET ) gene showed upregulation only at high Cd, low Cu, and high Cu. The expression of the enzymes glutathione reductase ( GR ), ascorbate peroxidase ( APX ), and catalase ( CAT ) was greatest at high Cu, and at high Cd and Cu together; the highest expression was under Cu, alone and combined. Both metals induced upregulation of the DNA methyltransferases CMT3 and DRM2, with the highest expression at single Cu. The DNA demethylation ROS1 was overexpressed in treatments containing high Cu, suggesting epigenetic modifications. The results show that under copper and/or cadmium, Z. marina was still biologically viable; certainly based, at least in part, on the induction of metal chelators, antioxidant defences and methylation/demethylation pathways of gene regulation. Highlights: Cu accumulation is always higher than Cd, under single and combined treatments. GSH and PCs levels increased upon the accumulation of Cd and/or Cu. Zostera marina displayed up to PC5 under Cd and/or Cu exposure. Expression of GR, APX and CAT was the greatest under Cu, alone or combined with Cd. Expression of CMT, DRM2 and ROS1 showed epigenetic-mediated tolerance mechanisms.